Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metals in surface sediment of a reservoir in northwest China - Yufeng Xie; Ming Kong; Fei He; Rongrong Ying; Tao Long (Ecological Indicators)
In order to explore the distribution pattern of heavy metal risks in surface sediments of Mengjin Reservoir in Xinjiang, China, different risk level evaluation methods were used for analysis. The pollution index analysis shows that the heavy metals in the surface sediment of the reservoir are at an uncontaminated level, but arsenic (As) is within the pollution alert range; The potential ecological hazard index method shows that mercury (Hg) and cadmium (Cd) are the main ecological hazard contributing factors; Correlation analysis and principal component analysis suggest that As and Pb are mainly affected by human activities, while heavy metals chromium (Cr) and copper (Cu) mainly come from natural sources, while other heavy metals are simultaneously affected by both human activities and natural sources. The research results can provide decision support for preventing pollution in reservoirs and ensuring water quality safety.